O crime organizado e o fenómeno do terrorismo no Brasil - Dallago, Renzo Medina (2020)
This thesis aims to analyze the relationship between organized crime and the phenomenon of terrorism in Brazil, from 1964 to nowadays. Thus, the problem that guides this research is presented in the following question: Is there a relationship between the points faced and discussed by Brazilian congressmen throughout the Legislative Process that culminated in the sanction of Federal Law nº. 13.260, of March 16, 2016 and the criminal organizations in Brazil, especially the First Command of the Capital (PCC)? It is hypothesized, therefore, that organized crime acts in Brazil with a modi operandi similars to the main world terrorist organizations, however, with different objectives and purposes. It deals with the phenomenon of world terrorism, its history and its distinctions, presenting the theoretical arguments of Bruce Hoffman, Audrey Cronin, Jorge Bacelar Gouveia, among others, as well as concepts about the phenomenon of terrorism of state agencies like the CIA, FBI and supranational organization like the North Atlantic Treaty Organization (NATO). Shortly thereafter, the Brazilian legislative process is approached, from the first bill on terrorism to the sanction of Federal Law nº. 13.260/2016. Finally, the research is instrumentalized by the cross-check between the justifications presented by Brazilian congressmen and the reality lived in the country, especially the last 30 years, a period corresponding to redemocratization, taking into account the theoretical analysis of the phenomenon of criminal terrorism. and social banditry, and information is presented to the reader concerning the criminal organizations operating in Brazil – expanding to Latin American and European countries, in particular the PCC, as well as notes, graphs, reports, figures and even the PCC Statute materially corroborating the initial hypothesis.